المراكز العلمية في مدينة القدس في عصر دولة المماليك البرجية (784ه /922م -1382-1516م) (Albayan Scientific Journal, 2023)
This study discusses the circumstances of knowledge activities in the Jerusalem city throughout the history of the Mamluks kingdom. Also, it is to explore the educational system in the Jerusalem, its significant factors and how far the Islamic endowment facilitates the academic activities and help preserve religious and academic institutions from collapse. Likewise, it is to investigate the pyramid of function and knowledge of the academic institutions in the city and its reflection in the civilizational progress and the prolific scholars of the Jerusalem.